Incidence and risk factors of phlebitis among adult patients with peripheral intravenous catheter (PIVC) - Mohamad, Fatimah; Daud, Azlina; Sowtali, Siti Noorkhairina (2017)
Background of study: The insertion of peripheral intravenous catheter (PIVC) is essential among hospitalized patients for treatment purposes. However, this procedure usually fails before the end of therapy due to many complications. Phlebitis is one of the common complication occurred. Therefore, this study was conducted to determine the incidence rate of phlebitis among patients with PIVC and identify the associated risk factors contributed to phlebitis.